Current state of ichthiocenosis, species composition and fish populations in small river basins from Pripyatske Polissiya of Ukraine — ways of rehabilitation and restoration - V. Sondak; O. Volkoshovetz; N. Kolesnik; M. Simon (Ribogospodarsʹka Nauka Ukraïni, 2020)
Purpose. To study ichthyocenosis, species composition and current state of fish populations in small river basins from Pripyatske Polissiya of Ukraine, to propose the ways of their rehabilitation and restoration.